The 60th anniversary of Ivan Vakarchuk (Condensed Matter Physics, 2007)
Professor Ivan Vakarchuk is a well-known Ukrainian physicist internationally recognized among theoreticians owing to his works on quantum liquids, phase transitions and critical phenomena, disordered systems and quantum mechanics. Being the author of 230 scientific papers and 5 textbooks, he is widely known for having developed various approaches and techniques in theoretical studies of many-particle quantum systems as well as a brilliant lecturer in theoretical physics.